Influence of varieties and nutrient management practices on productivity, nutrient acquisition and resource-use efficiency of rice (Oryza sativa) in North-eastern hill region of India - HARISH M N; ANIL K CHOUDHARY; Y V SINGH; VIJAY POONIYA; ANUP DAS; VARATHARAJAN T; SUBHASH BABU (The Indian Journal of Agricultural Sciences, 2019)
It is concluded that the INM practice and rice variety Shahsarang 1 showed their superiority over their respective counterparts, i.e. other nutrient management practices and rice varieties w.r.t. crop productivity, NPK acquisition behavior in rice grains and straw vis–à–vis NPK uptake, and resource–use efficiency in current study. Thus, INM practice and rice variety Shahsarang 1 can be recommended to the resource-poor hill farmers for enhancing rice productivity, plant nutrient acquisition and resource–use efficiency in north-eastern hill region of eastern Himalayas.